Evaluation of the Acceptability of a Prenatal Program for Women With Histories of Childhood Trauma: The Program STEP - Berthelot, Nicolas; Drouin-Maziade, Christine; Garon-Bissonnette, Julia; Lemieux, Roxanne; Sériès, Thibaut; Lacharité, Carl (Frontiers in Psychiatry, 2021)
Background: Childhood trauma would negatively affect pregnant women’s mental health and would have intergenerational repercussions. However, there is a paucity of prenatal interventions specifically designed for women exposed to childhood trauma. The study aims to evaluate the acceptability of STEP, a manualized group intervention designed for pregnant women having experienced early life adversity. Methods: The acceptability of STEP was assessed in four phases. In Phase 1, six experts evaluated whether the program activities were pertinent and trauma sensitive. In Phase 2, three parents read the intervention manuals and evaluated whether they considered each session relevant, interesting, and clear. In Phase 3, the program was briefly presented by phone to 309 pregnant women from the community. Women were inquired about their interest in the program, and the reasons for their lack of interest were assessed. In Phase 4, 30 pregnant women exposed to childhood trauma participated in the program and completed anonymous satisfaction questionnaires after each session. Psychological distress was also measured before and after the program. Results: All activities were rated by independent experts as highly pertinent, adequate, and sufficiently safe to be offered to pregnant women. Parents who read through the intervention manuals also considered that the sessions were relevant, clear and interesting. About half of the pregnant women from the community showed interest in the program. Participants reported very high levels of satisfaction and a significant decrease in psychological distress during the program. Conclusions: Our findings show a high level of convergence among various indicators of program acceptability.